Staphylococcus epidermidis and Staphylococcus haemolyticus: detection of biofilm genes and biofilm formation in blood culture isolates from patients in a Brazilian teaching hospital - Pinheiro, Luiza [UNESP]; Brito, Carla Ivo [UNESP]; Oliveira, Adilson de [UNESP]; Pereira, Valéria Cataneli [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (Elsevier, 2016)
Infections with coagulase-negative staphylococci are often related to biofilm formation. This study aimed to detect biofilm formation and biofilm-associated genes in blood culture isolates of Staphylococcus epidermidis and S. haemolyticus. Half (50.6%) of the 85 S. epidermidis isolates carried the icaAD genes and 15.3% the bhp gene, while these numbers were 42.9% and 0 for S. haemolyticus, respectively. According to the plate test, 30 S. epidermidis isolates were biofilm producers and 40% of them were strongly adherent, while only one (6%) of the 17 S. haemolyticus biofilm-producing isolates exhibited a strongly adherent biofilm. The concomitant presence of icaA and icaD was significantly associated with the plate and tube test results (P ≤ 0.0004). The higher frequency of icaA in S. epidermidis and of icaD in S. haemolyticus is correlated with the higher biofilm-producing capacity of the former since, in contrast to IcaD, IcaA activity is sufficient to produce small amounts of polysaccharide. Although this study emphasizes the importance of icaAD and bhp for biofilm formation in S. epidermidis, other mechanisms seem to be involved in S. haemolyticus.
Keywords: bhp; Biofilm; ica genes; Staphylococcus epidermidis; Staphylococcus haemolyticus